2000
DOI: 10.1046/j.1523-1755.2000.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal serum β2-microglobulin predicts postnatal renal function in bilateral uropathies

Abstract: Fetal serum beta2-microglobulin is a marker for renal function and predicts postnatal serum creatinine in bilateral or low fetal obstructive uropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 23 publications
0
52
0
6
Order By: Relevance
“…It is excreted by the kidney without placental cross-over so that fetal levels represent fetal renal function. One can see an elevation in renal dysplasia (45). Other urinary constituents commonly associated with the presence of renal disease include proteins such as albumin, retinol binding protein, and N-acetyl-b-glucosaminidase have been studied (45).…”
Section: Fetal Urine and Amniotic Fluid Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is excreted by the kidney without placental cross-over so that fetal levels represent fetal renal function. One can see an elevation in renal dysplasia (45). Other urinary constituents commonly associated with the presence of renal disease include proteins such as albumin, retinol binding protein, and N-acetyl-b-glucosaminidase have been studied (45).…”
Section: Fetal Urine and Amniotic Fluid Testingmentioning
confidence: 99%
“…One can see an elevation in renal dysplasia (45). Other urinary constituents commonly associated with the presence of renal disease include proteins such as albumin, retinol binding protein, and N-acetyl-b-glucosaminidase have been studied (45). Unfortunately human fetal urine sampling lacks known control normals at different stages of development.…”
Section: Fetal Urine and Amniotic Fluid Testingmentioning
confidence: 99%
“…However, data on the prediction of postnatal morbidity based on fetal serum β2M levels remain scarce. Indeed, the number of fetuses investigated to date is small and the study population heterogeneous, comprising both unilateral and bilateral uropathies and nephropathies [10]. Fetal serum β2M is a marker for renal function and predicts postnatal serum creatinine in bilateral or low fetal obstructive uropathy [10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the number of fetuses investigated to date is small and the study population heterogeneous, comprising both unilateral and bilateral uropathies and nephropathies [10]. Fetal serum β2M is a marker for renal function and predicts postnatal serum creatinine in bilateral or low fetal obstructive uropathy [10]. Studies have demonstrated higher urinary β2M concentrations in children with ureteropelvic junction obstruction compared with healthy controls [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Como discutido anteriormente, o estudo da bioquímica urinária fetal reflete a função tubular renal, pois avalia substâncias normalmente filtradas nos glomérulos e reabsorvidas nos túbulos (52,57 …”
Section: -Sangue Fetalunclassified